2017
DOI: 10.1111/pace.13173
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ICD lead on the system durability, predictors of long‐term survival following ICD system extraction

Abstract: ICD leads remain more vulnerable, with respect to mechanical failure and their propensity to infection, in comparison to pacing leads. Their TLE is very effective at least complication rate, when performed by a highly skilled and experienced operator. However, long-term mortality after their TLE is high and is affected mostly by infections or patient-related factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
(37 reference statements)
1
7
0
Order By: Relevance
“…Subjects with high‐voltage leads and multiple‐lead systems, and those with relatively shorter lead dwell times were also more susceptible to vegetations. Most of the above described factors were reported in earlier publications (Jacheć et al, 2017; Polewczyk, Jachec, Polewczyk, et al., 2017; Polewczyk, Jachec, Tomaszewski, et al., 2017).…”
Section: Discussionmentioning
confidence: 72%
“…Subjects with high‐voltage leads and multiple‐lead systems, and those with relatively shorter lead dwell times were also more susceptible to vegetations. Most of the above described factors were reported in earlier publications (Jacheć et al, 2017; Polewczyk, Jachec, Polewczyk, et al., 2017; Polewczyk, Jachec, Tomaszewski, et al., 2017).…”
Section: Discussionmentioning
confidence: 72%
“…The available evidence shows that CIED-related infection is the most common prognostic factor for unfavorable outcomes of TLE [5][6][7][8][9][10][11][13][14][15][17][18][19][20][21][22]. Other factors are mainly those dependent on the patient's general condition i.e., age [6,13,21,22], renal failure [5][6][7][8]10,12,13,16,[19][20][21][22], diabetes [5,16,21], heart failure [7,10,16,22], anemia [8,19], comorbidities [7]. Several studies have demonstrated the significance of procedure-related factors (system upgrade, ICD or CRT device, procedural failure, retained lead fragments, major complications, abandoned leads) [5,6,[11][12]…”
Section: Discussionmentioning
confidence: 99%
“…Other factors are mainly those dependent on the patient's general condition i.e., age [6,13,21,22], renal failure [5][6][7][8]10,12,13,16,[19][20][21][22], diabetes [5,16,21], heart failure [7,10,16,22], anemia [8,19], comorbidities [7]. Several studies have demonstrated the significance of procedure-related factors (system upgrade, ICD or CRT device, procedural failure, retained lead fragments, major complications, abandoned leads) [5,6,[11][12][13][14]16,21] (Table 5). Echocardiographic phenomena have been very rarely analyzed in terms of their impact on long-term survival after TLE A couple of papers showed only the role of so-called ghosts, i.e., post-removal, tubular, mobile masses following the lead's intracardiac route in the right-sided heart chambers [15,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A weak component of traditionally used ICD systems is the defibrillation lead, which is placed through the venous circulatory system into the right ventricle. It was shown that the longevity of defibrillation leads have become substantially reduced, and risk of infection is significantly higher compared to pacing leads [3]. The subcutaneous implantable cardioverter-defibrillator (S-ICD) was developed in response to endovascular lead complications and represents important progress in defibrillation technology.…”
Section: Introductionmentioning
confidence: 99%